PENGUKURAN KINERJA PERUSAHAAN MENGGUNAKAN METODE BALANCE SCORECARD (Studi Kasus Haus Indonesia) - Anarki, Rian Rambu; Suherman, Aji Mardiansyah; Pakaya, Martin Ramadhan; Augusto, Jordan; Rinaldo, Dito (STIE DWI SAKTI BATURAJA, 2024)
This research aims to determine the performance of HAUS Indonesia using the Balanced Scorecard approach. This research is descriptive research with a quantitative and qualitative approach using the Balanced Scorecard concept calculation for each Key Performance Indicator in four perspectives by comparing targets and achievements to produce the final score. The results of this research show that HAUS Indonesia's performance has achieved a good score or has achieved the specified target by getting a score of 3.322.